DENTAL MALPRACTICE: DE FACTO et DE IURE - Gheorghe Bălan; Adriana Bălan (Romanian Society of Oral Rehabilitation, 2014)
Dental malpractice is a topic considerably difficulty defined. Both de facto and de iure, there are many ways in which patients, dentists or lawyers perceive the general context of dental malpractice. This study aims to identify and emphasize various biomedical and legal aspects characteristic to the dental malpractice system in Romania. Although there were some major recent changes regarding the Romanian civil and criminal codes, the principles regarding the medical and dental malpractice system remain stable. These principles are characterized by certain ethical, professional and legal values. From in-between beneficence and non-malfeasance, to professional and institutional liabilities, going further to tort law and contract breaches, dental malpractice is built on a complex structure. Each dental practitioner should be able to deal with patients' complaints bearing in mind that such complaints, together with an injury or harm, can be precursors of litigation. In an era where dental medicine is governed by advanced technology and principles of evidence based medicine the standards of care grow higher giving way to potential negligence and professional misconduct.